Interploidy gene flow involving the sexual-asexual cycle facilitates the diversification of gynogenetic triploid Carassius fish - Tappei Mishina (Nature Portfolio, 2021)
Abstract Asexual vertebrates are rare and at risk of extinction due to their restricted adaptability through the loss of genetic recombination. We explore the mechanisms behind the generation and maintenance of genetic diversity in triploid asexual (gynogenetic) Carassius auratus fish, which is widespread in East Asian fresh waters and exhibits one of the most extensive distribution among asexual vertebrates despite its dependence on host sperm. Our analyses of genetic composition using dozens of genetic markers and genome-wide transcriptome sequencing uncover admixed genetic composition of Japanese asexual triploid Carassius consisting of both the diverged Japanese and Eurasian alleles, suggesting the involvement of Eurasian lineages in its origin. However, coexisting sexual diploid relatives and asexual triploids in Japan show regional genetic similarity in both mitochondrial and nuclear markers. These results are attributed to a unique unidirectional gene flow from diploids to sympatric triploids, with the involvement of occasional sexual reproduction. Additionally, the asexual triploid shows a weaker population structure than the sexual diploid, and multiple triploid lineages coexist in most Japanese rivers. The generated diversity via repeated interploidy gene flow as well as an increased establishment of immigrants is assumed to offset the cost of asexual reproduction and might contribute to the successful broad distribution of this asexual vertebrate.